2015 Physics Education Research Conference Proceedings 2015
DOI: 10.1119/perc.2015.pr.045
|View full text |Cite
|
Sign up to set email alerts
|

Determining strategies that predict physics identity: Emphasizing recognition and interest

Abstract: Although the number of students earning bachelor's degrees in physics has increased, the percentage of those degrees earned by women has not increased for more than 10 years. We use a physics identity framework to understand the factors that may impact physics career choice. Physics identity consists of three dimensions: recognition (perception of recognition by others), interest (desire to learn more), and performance/competence (perception of ability to understand). Our previous work has shown that recogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…The consistent use of graphs, pictures, and tables in physics problems by the instructor (Supplementary Material 3) could also be considered as one of the activities that might have enhanced the participants' interest in this study. This supports existing research findings that the use of questions involving graphs and strategies promoting conceptual understanding can positively predict interest as component of physics identity (Lock et al, 2015).…”
Section: Interestsupporting
confidence: 89%
See 1 more Smart Citation
“…The consistent use of graphs, pictures, and tables in physics problems by the instructor (Supplementary Material 3) could also be considered as one of the activities that might have enhanced the participants' interest in this study. This supports existing research findings that the use of questions involving graphs and strategies promoting conceptual understanding can positively predict interest as component of physics identity (Lock et al, 2015).…”
Section: Interestsupporting
confidence: 89%
“…Hence, by examining if an MR-based instructional approach influences the development of the components of physics identity, we aim to contribute to an existing knowledge gap about the kinds of instructional practices that might contribute to the development of physics identity. We maintain that the use of an MR-based instructional approach to physics teaching might contribute to the development of specific components of physics identity, because (a) MR might be used for the presentation of real-world problems in ways that enhance student interest and engagement (Ainsworth, 1999), (b) MR have the potential to enhance students' conceptual understanding and problem-solving skills (Kohl & Finkelstein, 2017;Sutopo, & Waldrip, 2014) which is directly related to both their competence and performance, and (c) the use of questions that involve graphs and tables correlates with interest and self-recognition (Lock et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…According to a case study of high school physics classrooms, forms of recognition have been found to include setting high expectations and giving challenging assignments while at the same time providing students with the necessary support to meet those expectations and challenges [25]. Another form of recognition has been found to create a classroom environment that provides opportunities for students to take on leadership roles and demonstrate their expertise [10,25]. Finally, teachers demonstrating to students that they care and that they are willing to invest time in their students is a way of showing that they believe that their students can do difficult work [25].…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…These experiences may impact young women and men differently as the cultural and social context of these experiences may convey different messages and support young women differently than men. In prior work, we examined the effects of in-class high school physics experiences on students' physics identities and career choices [7][8][9][10], and, in this paper, we examine the impact of out-of-class science and engineering (OCSE) activities, with attention to possible differential impacts on women. OCSE activities are a specific subset of out-of-school time (OST) activities.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of my study, physics identity can be thought of as the extent to which someone sees themselves as a "physics person" (Lock, Castillo, Hazari, & Potvin, 2015); likewise, someone with a strong math identity sees themselves as a "math person", and someone with a strong engineering identity sees themselves as an engineer. In the framework developed by Hazari et al, it is conceptualized as a quasi-trait-something which is relatively stable but which can change over time as a result of experiences (Cribbs, Sadler, Hazari, Conatser, & Sonnert, 2013;Hazari et al, 2010;.…”
Section: Identity Frameworkmentioning
confidence: 99%